Desain Perencanaan Instalasi Pengolahan Air Limbah Tambak Udang Vaname Intensif di CV X, Desa Campurejo, Panceng, Kabupaten Gresik - Moh Anshor; Rodu Dhuha Afrianisa; Taty Alfiah (Teknik Lingkungan, Institut Teknologi Adhi Tama Surabaya, 2026)
Intensive vannamei shrimp (Litopenaeus vannamei) farming produces wastewater with high organic and nutrient loads, which can contaminate surrounding waters without proper treatment. This study designs a Wastewater Treatment Plant (WWTP) for X Firm’s intensive shrimp ponds in Campurejo Village, Panceng District, Gresik Regency, ensuring the effluent meets the quality standards set by the Regulation of the Minister of Marine Affairs and Fisheries No. 28 of 2004. The design process uses laboratory test results of wastewater characteristics and operational analysis of the ponds. The Analytical Hierarchy Process (AHP) method determines treatment alternatives, identifying a combination of anaerobic–aerobic biofilter processes as the most effective based on technical feasibility, pollutant removal efficiency, and land requirements. The proposed WWTP includes an equalization pond, anaerobic biofilter 1, anaerobic biofilter 2, aerobic biofilter, and a final sedimentation pond. It has a treatment capacity of 1,405.7 m³/day, with retention times optimized for each unit. The design requires 534.88 m² of land. Keywords: WWTP, Intensive Vannamei Shrimp Farming, Anaerobic-Aerobic Biofilter, Wastewater, Gresik Regency